TRANSPERITONEAL LAPAROSCOPIC URETEROLITHOTOMY FOR LARGE DISTAL URETERIC STONE - Priyosantoso, Bacilius Agung; Pramod, Sawkar Vijay (Indonesian Urological Association, 2015)
Objective: This study is aim to share our experience (in videos) in Laparoscopic ureterolithotomy for large distal ureteric stone with transperitoneal approach. Material & methods: A 37 years old male has been diagnosed with a right hydronephrosis due to proximal ureterolithiasis and stone at left calyx inferior, first and stone migrated to right distal ureter on 12 hours prior surgery, in Hasan Sadikin Hospital Bandung. He underwent laparoscopic ureterolithotomy with transperitoneal approach. Results: We successfully perform laparoscopic ureterolithotomy with transperitoneal approach on a 37 years old male patient who diagnosed with a right hydronephrosis due to distal ureterolithiasis and stone at left calyx inferior. Duration of operation was 45 minutes. Patient was discharged at 2nd postoperative day without any complications. Conclusion: A transperitoneal laparoscopic ureterolithotomy for distal ureteric stone is a safe and feasible technique that should be an options on every patients who is planning to undergo distal ureterolithotomy especially large stone. Keywords: Transperitoneal, laparoscopy, distal ureterolithotomy.